A consistent quantum field theory from dimensional reduction. (28th April 2023) - Maiezza, Alessio; Carlos Vasquez, Juan
Abstract: We incorporate the concept of dimensional reduction at high energies within the perturbative formulation of quantum field theory (QFT). In this new framework, space and momentum integrations are modified by a weighting function incorporating an effective mass energy associated with the dimensional reduction scale. We quantize the theory within canonical formalism. We then show that it can be made finite in perturbation theory, free of renormalon ambiguities, and with better analytic behavior for infinitesimal coupling constant compared to standard QFT. The new approach reproduces the known results at low energies. One key feature of this class of models is that the coupling constant always reaches a fixed point in the ultraviolet (UV) region, making the models UV complete.